Developmentally regulated expression of an exon containing a stop codon in the gene for glutamic acid decarboxylase. - Bond, R W (1990)
In the adult rat brain, the gene for glutamic acid decarboxylase (GAD; L-glutamate 1-carboxy-lyase, EC 4.1.1.15) is expressed predominantly as a 3.7-kilobase transcript. Earlier data showed that embryonic brain expresses an RNA transcript distinct from the adult form; however, the exact structure of this form was not elucidated. Here, transcripts expressed in the embryonic but not the adult brain were cloned and analyzed. These transcripts include an exon not expressed in the adult inserted into coding sequence. The embryonic exon contains a stop codon that is in-frame with the coding sequence. The exon is found in genomic DNA within the GAD gene where it is flanked by introns with conventional splice sites. On the basis of these structural data, we propose the hypothesis that, early in brain development, transcripts encoding a truncated form of GAD are expressed. The deduced protein cannot function as a decarboxylase because the stop codon in the embryonic exon occurs upstream of the binding site for pyridoxal phosphate, an essential cofactor. Thus, alternative splicing plays a crucial role in the pathway leading to the development of functional GABAergic neurons. The central nervous system-derived cell lines B65 and C6 express a mixture of the adult and embryonic forms of GAD mRNA. They therefore are useful clonal models of central nervous system cells in the early phases of differentiation.